Prioritizing mental health support for physician-scientist trainees - Jasmine A. Tuazon; Ammar D. Siddiqi; Randal A. Serafini; Clayton D. Rawson; Rohini N. Guin; Brad A. Ryva; Jessica L. Ding (Communications Medicine)
Physician-scientist trainees’ dual commitment to advancing medicine and undertaking research predisposes them to mental health challenges. Here, we outline the critical gaps in mental health support structures available to this unique trainee population and provide recommendations to reduce the concerns discussed.